Estimates of National Income 1948-49 to 1962-63 - Planning Commission (Planning Commission, 1964)
This paper brings up to 1962-63 the series of national income for the Indian Union including Jammu and Kashmir. The preliminary estimates for 1961-62 as also the quick estimates for 1962-63 at constant prices, published earlier by this Organisation, have undergone upward revision partly due to similar upward revision of agricultural production estimates and partly due to the incorporation, for the first time, of the results of random crop cutting surveys in respect of sugarcane in Punjab.
Central Statistical Organisation, Department of Statistics, Cabinet Secretariat, Government of India